NUMERICAL ANALYSIS OF LIFT AND PRESSURE COEFFICIENTS OF AN AIRFOIL: ANSYS VS SOLIDWORKS - Spaseski, Igor; Pezdevšek, Marko; Ščuri, Igor; Fike, Matej; Hren, Gorazd (Journal of Energy Technology, 2024)
In this article, curves for the lift and pressure characteristics of an NACA 6508 airfoil at various angles of attack were acquired with numerical simulation software packages: Ansys CFX and Solid-Works Flow Simulation. The analyses were performed using three different mesh resolutions, with similar number of elements, for different angles of attack. Furthermore, all numerically obtained results were compared to the experimental measurements from a reliable source.